Chemical etching of nitinol stents - Katona, Bálint; Bognár, Eszter; Berta, Balazs; Nagy, Péter; Hirschberg, Kristóf (Acta of bioengineering and biomechanics, 2013)
At present the main cause of death originates from cardiovascular diseases. Primarily the most frequent cause is vessel closing thus resulting in tissue damage. The stent can help to avoid this. It expands the narrowed vessel section and allows free blood flow. The good surface quality of stents is important. It also must have adequate mechanical characteristics or else it can be damaged which can easily lead to the fracture of the implant. Thus, we have to consider the importance of the surface treatment of these implants. In our experiments the appropriate design was cut from a 1.041 mm inner diameter and 0.100 mm wall thickness nitinol tube by using Nd:YAG laser device. Then, the stent was subjected to chemical etching. By doing so, the burr created during the laser cutting process can be removed and the surface quality refined. In our research, we changed the time of chemical etching and monitored the effects of this parameter. The differently etched stents were subjected to microscopic analysis, mass measurement and in vivo environment tests. The etching times that gave suitable surface and mechanical features were identified.